Secular Trends on Birth Parameters, Growth, and Pubertal Timing in Girls with Turner Syndrome - Woelfle, Joachim; Lindberg, Anders; Aydin, Ferah; Ong, Ken K.; Camacho-Hubner, Cecilia; Gohlke, Bettina (Frontiers in Endocrinology, 2018)
Background Whether children with chromosomal disorders of growth and puberty are affected by secular trends (STs) as observed in the general population remains unanswered, but this question has relevance for expectations of spontaneous development and treatment responses. Objectives The aim of the study was to evaluate STs in birth parameters, growth, and pubertal development in girls with Turner syndrome (TS). Study design Retrospective analysis of KIGS data (Pfizer International Growth Database). We included all TS patients who entered KIGS between 1987 and 2012 and were born from 1975 to 2004, who were prepubertal and growth treatment naïve at first entry (total number: 7,219). Pretreatment height and ages at the start of treatment were compared across 5-year birth year groups, with subgroup analyses stratified by induced or spontaneous puberty start. Results We observed significant STs across the birth year groups for birth weight [+0.18 SD score (SDS), p < 0.001], pretreatment height at mean age 8 years (+0.73 SDS, p < 0.001), height at the start of growth hormone (GH) therapy (+0.38 SDS, p < 0.001) and start of puberty (+0.42 SDS, p < 0.001). Spontaneous puberty onset increased from 15 to 30% (p < 0.001). Mean age at the start of GH treatment decreased from 10.8 to 7.4 years (−3.4 years; p < 0.001), and substantial declines were seen in ages at onset of spontaneous and induced puberty (−2.0 years; p < 0.001) and menarche (−2.1 years; p < 0.001). Conclusion Environmental changes leading to increased height and earlier and also more common, spontaneous puberty are applicable in TS as in normal girls. In addition, greater awareness for TS may underlie trends to earlier start of GH therapy and induction of puberty at a more physiological age.